2005
DOI: 10.17660/actahortic.2005.682.118
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pre- And Postharvest Calcium Applications on ´hayward´ Kiwifruit Storage Ability

Abstract: The benefits of calcium applications pre and postharvest on fruit storage ability have been mentioned in the bibliography. It was objective of this work to study the effect of calcium preharvest application in two different forms and calcium chloride application postharvest on 'Hayward' kiwifruit storage ability.Kiwifruit vines were sprayed with 0.03% CaCl 2 or 0.03% CaO at one, three and four months before harvest. The control did not have any treatment. After harvest, half fruits were dipped for 2 min in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Previous studies have already demonstrated the capacity of calcium to delay softening in kiwifruit , . Several factors may contribute to this property: the ability of calcium to cross-link with carboxyl groups of polyuronide chains of pectins , the possibility of calcium delaying galactolipid breakdown, increasing the rate of sterol conjugation, being important in membrane organization and function , , and acting on cell turgor pressure .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have already demonstrated the capacity of calcium to delay softening in kiwifruit , . Several factors may contribute to this property: the ability of calcium to cross-link with carboxyl groups of polyuronide chains of pectins , the possibility of calcium delaying galactolipid breakdown, increasing the rate of sterol conjugation, being important in membrane organization and function , , and acting on cell turgor pressure .…”
Section: Resultsmentioning
confidence: 99%
“…Pre and postharvest calcium application has been demonstrated to produce beneficial effects on whole fruit quality, decreasing the incidence of physiological disorders (Gerasopoulos & Drogoudi, 2005;Manganaris, Vasilakakis, Diamantidis, & Mignani, 2007;Serrano, Martínez-Romero, Castillo, Guillén, & Valero, 2004), mould growth (Naradisorn, Klieber, Sedgley, Scott, & Able, 2006) and delaying softening (Antunes, Panagopoulos, Rodrigues, Neves, & Curado, 2005;García, Herrera, & Morilla, 1996;Naradisorn et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Ca plays a significant role in maintaining quality in a number of different fruits (Hopkirk et al, 1990). Pre-and postharvest Ca application has been demonstrated to produce beneficial effects on whole fruit quality, decreasing the incidence of physiological disorders (Serrano et al, 2004) and delaying softening (Antunes et al, 2004). Ca is directly involved in strengthening plant cell walls through its ability to crosslink with carboxyl groups of polyuronide chains of pectins found in the middle lamella (Lara et al, 2004).…”
mentioning
confidence: 99%